2020
DOI: 10.1007/s00221-020-05919-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-selective inhibition of the motor system following unexpected and expected infrequent events

Abstract: Motor inhibition is a key control mechanism that allows humans to rapidly adapt their actions in response to environmental events. One of the hallmark signatures of rapidly exerted, reactive motor inhibition is the non-selective suppression of cortico-spinal excitability (CSE): unexpected sensory stimuli lead to a suppression of CSE across the entire motor system, even in muscles that are inactive. Theories suggest that this reflects a fast, automatic, and broad engagement of inhibitory control, which facilita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 66 publications
7
28
0
Order By: Relevance
“…This is in line with the proposal that this ERP reflects a process that is unique to outright action-stopping (de Jong et al, 1990;Kok et al, 2004), and with the proposal that the onset latency of this ERP index the onset of processing that distinguishes successful from failed stopping (Wessel & Aron, 2015). Second, with regards to CSE suppression, these results confirm earlier studies showing that such effects can be observed not just after STOP signals, but also after surprising or merely infrequent events Dutra et al, 2018;Iacullo et al, 2020). The current results substantially add to these findings by demonstrating that STOP signals and IGNORE signals do not differ in the degree to which they suppress CSE early on (here, at 150ms post-stimulus).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is in line with the proposal that this ERP reflects a process that is unique to outright action-stopping (de Jong et al, 1990;Kok et al, 2004), and with the proposal that the onset latency of this ERP index the onset of processing that distinguishes successful from failed stopping (Wessel & Aron, 2015). Second, with regards to CSE suppression, these results confirm earlier studies showing that such effects can be observed not just after STOP signals, but also after surprising or merely infrequent events Dutra et al, 2018;Iacullo et al, 2020). The current results substantially add to these findings by demonstrating that STOP signals and IGNORE signals do not differ in the degree to which they suppress CSE early on (here, at 150ms post-stimulus).…”
Section: Discussionsupporting
confidence: 90%
“…The copyright holder for this preprint this version posted February 27, 2021. ; https://doi.org/10.1101/2021.02.26.433098 doi: bioRxiv preprint Non-selective CSE suppression. We first aimed to replicate the established findings of nonselective CSE suppression in the task related muscle following both STOP (Badry et al, 2009) and IGNORE signals (Iacullo et al, 2020). As can be seen in Figure 3 Time, there was only anecdotal evidence to support this difference (BF10 = 1.28, t(27) = 1.86, pHolm = .068, d = .35).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations